Eco-friendly, natural dyeing of linen, ramie, and hemp fabrics using Polygonum tinctoria - Kim, Mikyoung (The Research Journal of the Costume Culture, 2023)
In this study, natural dyeing using Polygonum tinctoria was performed with linen, ramie, and hemp, which are biodegradable cellulose fibers, considering environmental aspects. In particular, the impacts of alkali NaOH and reducing agent Na2S2O4 were examined, and the possibilities of minimizing the use and reusing the dye were explored. The surface dye concentrations were found to be in the following order: hemp>linen>ramie. With the increase in all additives, the L* value decreased, and the ⊿E and K/S values increased gradually. When Na2S2O4 was 1g/L, the surface color of the dye appeared uniformly from the NaOH concentration of 0.4g/L (pH 10.84). When NaOH was 0.4g/L, the K/S values of linen and ramie increased rapidly after 0.4g/L of Na2S2O4, and hemp maintained a stable color from 0.6g/L of Na2S2O4. With the increase in the dye concentration from 1 to 6g/L, all the fibers were dyed uniformly. The K/S value increased or higher doubled upon repeated dyeing six times for 5 min than when dyed only once for 30 min. Therefore, the linen, ramie, and hemp fibers dyed repeatedly exhibited good washing, rubbing, and colorfastness to perspiration, which was rated between 4 and 4–5, and that to light was rated as 5. Moreover, no discoloration due to sunlight was observed. Finally, linen exhibited a bacterial reduction of 99.9%, thereby indicating its excellent antibacterial property.